Adaptation and validation of the Collective Efficacy Questionnaire for Sport (CEQS) in Arabic: enhancing team dynamics assessment - Jaouher Hamaidi; Mohamed Mansour Bouzourraa; Mouna Saidane; Mohamed Ben Aissa; Mohamed Ali Boujelbane; Khaled Trabelsi; Haitham Jahrami; Achraf Ammar; Noomen Guelmami; Makrem Zghibi; Ismail Dergaa (Cogent Social Sciences)
The Arabic adaptation of the CEQS addresses the pressing need in sports psychology, allowing assessment of collective efficacy in Arabic-speaking teams and facilitating cross-cultural comparisons of team dynamics. This study undertook a rigorous translation and back-translation process for the CEQS, engaging athletes from a variety of sports in both exploratory (n = 477) and confirmatory (n = 510) phases. Exploratory and confirmatory factor analyses (EFA and CFA) were used to evaluate the factor structure, while reliability was assessed through Cronbach’s alpha and McDonald’s omega. Concurrent validity was established by correlating A-CEQS scores with measures of team performance and communication, and sensitivity was examined through the scale’s ability to distinguish between novice and experienced players. The A-CEQS demonstrated exceptional reliability across its subscales (Cronbach’s alpha and McDonald’s omega >0.9), with EFA identifying a factor structure consistent with the original scale. CFA supported the model’s fit (χ2(190) = 10998.745, p < 0.001; RMSEA = 0.040 [0.033–0.047]; CFI = 0.987; TLI = 0.986; GFI = 0.942; AGFI = 0.928). Concurrent validity was confirmed through significant correlations with Coach–Athletes relationships. The A-CEQS is a reliable measure of collective efficacy in Arabic-speaking sports teams. It enables cross-cultural research and practical applications for enhancing team performance and dynamics.